Cooperative Communication in Cognitive Radio Networks under Asymmetric Information: A Contract-Theory Based Approach - Nan Zhao; Minghu Wu; Wei Xiong; Cong Liu (International Journal of Distributed Sensor Networks)
By exploiting the spatial diversity of multiple wireless nodes, cooperative communication technique is a promising technique for spectrum sharing to improve spectrum efficiency. In this paper, the incentive issue between relay nodes' (RNs') service and source's relay selection is investigated in the presence of the asymmetric information scenario. Multiuser cooperative communication is modelled as a labour market, where the source designs a contract and each relay node decides to select a contract item according to hidden information in order to obtain the best profit. The optimal contract design under both symmetric information and asymmetric information is presented based on contract theory. The contract-theoretic model for ability discrimination relay selection is formulated as an optimization problem to maximize the source's utility. A sequential optimization algorithm is proposed to obtain the optimal relay-reward strategy. Simulation results show that the optimal contract design scheme is effective in improving system performance for cooperative communication. This paper establishes a valuable cooperative communication mechanism in cognitive radio networks.